Flexural Strength of Vitreous Ceramics Based on Lithium Disilicate and Lithium Silicate Reinforced with Zirconia for CAD/CAM - Corado, Hazel P. R.; da Silveira, Pedro H. P. M.; Ortega, Vagner L.; Ramos, Guilherme G.; Elias, Carlos N. (International Journal of Biomaterials, 2022)
The dental prosthesis market is rapidly evolving to meet patient and clinical demands. These new materials must have good flexural strength, toughness, aesthetic properties, and reliability in performance for structural applications. The present work aimed to compare the bending strength of 4 types of chairside lithium disilicate (Li2Si2O5) glass-ceramics used for dental prosthesis and to analyze the influence of heat treatment on the transformation of lithium metasilicate (Li2SiO3) into lithium disilicate. The three-ball test for the biaxial flexion test (B3B) was used. Weibull statistical analysis was used, and it showed that samples with a higher percentage of zirconia have a greater tendency to fail. The flexion tests showed that the addition of more than 10% of zirconia reduced the flexural strength. The heat treatment process improves and provides greater mechanical strength. The XRD results indicated that the samples with the lowest percentage of zirconia exhibited greater crystallinity and corroborated the microstructural analysis. SEM analyses showed a greater amount and elongated crystals of lithium disilicate when comparing samples with a higher percentage of zirconia. Therefore, samples with lower zirconia showed greater flexural strength than samples with higher additions of zirconia.